293. Concurrent Atlantoaxial Septic Arthritis and Septic Thrombosis of the Ophthalmic Vein due to Staphylococcus aureus: A Case Report and Review of the Literature. (26th November 2018) - Hajar, Zeina; Fotedar, Neel; Jump, Robin
Abstract: Background: Atlantoaxial joint septic arthritis and superior ophthalmic vein thrombosis (SOVT) are uncommon sequelae of infections. Here, we describe a patient who presented concurrently with two uncommon manifestations of a common pathogen, methicillin-susceptible Staphylococcus aureus (MSSA), and review the associated literature. A 68-year-old man presented to the hospital with a 4-day history of worsening neck pain, right shoulder pain, and one episode of diplopia. He reported left wrist pain and swelling 3 weeks prior to presentation. A whole body 18 F-positron emission tomography scan detected abnormal hypermetabolic activity in the atlantoaxial joint and in the right shoulder (Figure 1A and B). Magnetic resonance imaging revealed the presence of right SOVT (Figure 1C and D). Blood cultures grew MSSA. He underwent debridement of his right shoulder and was started on intravenous cefazolin. Conservative management of his atlantoaxial septic arthritis was unsuccessful and several weeks into his antibiotic course, he developed right-arm weakness for which he underwent C4 fusion to address atlanto-axial instability. Methods: We reviewed previous reports describing atlantoaxial septic arthritis ( n = 6) and septic ophthalmic vein thrombosis ( n = 6). Results: Previous reports of atlantoaxial septic arthritis detailed clinical presentations of subacute to acute onset of neck pain with fever, five of which were due to S. aureus . Four of the cases required a surgical intervention involving the cervical spine. Previous reports of SOVT describe patients ipsilateral proptosis, ptosis and chemosis. In all six cases, the SOVT developed in concurrence with a head and neck infections. Three cases required surgery or an interventional procedure for source control Two cases recovered completely and three cases improved but with diplopia or permanent loss of vision in the affected eye. Conclusion: Even with early recognition and prompt initiation of antibiotic therapy, our patient still suffered from long-term sequelae atlantoaxial septic arthritis and SOVT, a testament to the potential for MSSA to cause severe infections. Disclosures: All authors: No reported disclosures.